Epidemiology of antibiotic consumption and resistance in Mauritius - Veerapa-Mangroo, Lovena Preeyadarshini; Rasamoelina-Andriamanivo, Harena; Issack, Mohammad Iqbal; Cardinale, Eric (Frontiers in Antibiotics, 2024)
Introduction: This study aims at determining the pattern of antibiotic consumption and resistance in Mauritius, a tropical island in the Indian Ocean. Methodology: Antibiotic consumption was measured in kilograms of purchased antibiotics and also in Defined Daily Dose (DDD) in the different health institutions from 2015 to 2017. Data on antibiotic resistance was collected at the Central Health Laboratory (CHL) at Victoria Hospital and at Jeetoo Hospital Laboratory, where Antibiotic Sensitivity Testing is done for all public health institutions. For this study, Escherichia coli, Klebsiella species, Acinetobacter species and Pseudomonas aeruginosa isolates from blood samples of patients were included from 2015 to 2023. The resistance rate and prevalence of Multi-Drug Resistant (MDR) organisms were calculated. Results: The amount of antibiotics in kilograms distributed to the human sector was between 11000 to 13000 kg, compared to only 700 to 1500 kg in the animal sector. The DDD per 1000 inhabitants per day was 20.9, 22.1 and 21.7 in 2015, 2016 and 2017 respectively, with a greater consumption of WATCH and RESERVE group antibiotics in the private sector. In public health institutions, health centers in the northern region had the highest DDD per 1000 outpatients per day for beta-lactams penicillins and quinolones . Concerning antibiotic resistance, the proportion of MDR Acinetobacter baumannii and Pseudomonas aeruginosa has increased from 58% to 74% and from 33% to 45% respectively from 2015 to 2023. During the same period, the proportion of E.coli and K.pneumoniae isolates sensitive to ceftriaxone decreased from 55% to 39% and from 37% to 22% respectively, while the proportion of E.coli, Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa isolates sensitive to meropenem decreased from 98% to 94%, 83% to 53%, 45% to 28% and 63% to 47% respectively. Conclusion: This study provides valuable insights on antibiotic consumption and resistance in the country and emphasizes the significance of adopting a One Health approach to combat AMR effectively. These findings will aid policymakers in formulating targeted strategies to address the challenge of AMR and should be integrated into the National Action Plan on Antimicrobial Resistance (AMR) in Mauritius.